Deep Learning Training as a Pedagogical Transformation Strategy in Indonesia: Analysis of the Philosophical Framework and Technical Guidelines Based on the Decree of the Director General of Teachers, Education Personnel, and Teacher Education Number 13/B/HK.03.01/2025 - Yulia Fitri; Veithzal Rivai Zainal; Azis Hakim (Dinasti Publisher, 2025)
This study aims to analyze the philosophical framework of Deep Learning and examine the operational implications of training guidelines that adopt the In-Service Learning (IN-1) - On-the-Job Training (ON) - In-Service Learning (IN-2) model. The Director General of Teachers, Education Personnel, and Teacher Education Decision No. 13/B/HK.03.01/2025 concerning Technical Guidelines for Deep Learning Training (PM) is a formal state strategy to encourage holistic pedagogical transformation in Indonesia. The main objective of PM is to create conscious, meaningful, and enjoyable learning through the integrated development of thinking, heart, feelings, and body. The methods used are qualitative policy analysis and comparative literature studies. The results of the study show that PM is an innovative framework that requires the integration of the cognitive dimension (mind) with the affective- spiritual dimension (heart and senses), which substantially depends on the internalization of the Growth Mindset in teachers. The IN-ON-IN training model is an effort to mitigate the failure of knowledge transfer to practice (Kirkpatrick Level 3), but its success is greatly influenced by ecosystem support, including the quality assurance of resource persons and the functionality of the Learning Management System (LMS), as well as the school's ability to mitigate the digital divide. Recommendations that can be given include the need to develop standardized observation instruments that are capable of measuring emotional intelligence in the classroom, curating resource persons with growth mindset criteria, and providing equivalent blended learning alternatives.